Fintech syariah dan Transformasi Ekonomi Digital: Tinjauan Hukum Ekonomi Islam - Abdul Husain Natsir; Nasrullah Sapa (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The rapid development of financial technology (fintech) in the digital era presents both opportunities and challenges for the Islamic economic system. This study aims to analyze the concept of Islamic fintech, its role in digital economic transformation, and its legal review from the perspective of Islamic economic law (fiqh muamalah). Using a qualitative method with a normative juridical approach, this research examines various fintech models operating on sharia principles—including Islamic peer-to-peer (P2P) lending, digital Islamic crowdfunding, sharia payment gateways, and Islamic robo-advisory—and reviews their compliance with the principles of prohibition of riba (usury), gharar (excessive uncertainty), maysir (gambling), and the requirement of maslahah (public benefit). The results indicate that: (1) Islamic fintech represents a legitimate financial innovation insofar as it adheres to the principles of sharia; (2) the National Sharia Council–Indonesian Ulema Council (DSN-MUI) fatwas, particularly No. 117/DSN-MUI/II/2018 on Information Technology-Based Financing Services, provide a regulatory framework but require continuous updating to keep pace with technological developments; (3) Islamic fintech contributes significantly to financial inclusion, particularly for unbanked communities in Indonesia; and (4) challenges related to sharia compliance, data governance, and regulatory harmonization remain critical issues requiring the joint attention of regulators, sharia scholars, and technology practitioners. This study contributes to the development of Islamic economic law theory in the context of digital transformation and provides practical recommendations for Islamic fintech stakeholders.